Infection of Mycobacterium tuberculosis Promotes Both M1/M2 Polarization and MMP Production in Cigarette Smoke-Exposed Macrophages - Le, Yanqing; Cao, Wenli; Zhou, Lu; Fan, Xin; Liu, Qiangui; Liu, Fusheng; Gai, Xiaoyan; Chang, Chun; Xiong, Jing; Rao, Yafei; Li, Aling; Xu, Wei; et al. (Frontiers in Immunology, 2020)
Pulmonary tuberculosis (PTB) is a risk factor for COPD. Our previous study revealed more severe emphysema in COPD patients (mostly smokers) with prior tuberculosis. However, the mechanisms of interactions between cigarette smoke (CS) and mycobacterium tuberculosis (Mtb) are unknown. In this study, we found that the frequencies of both M1 and M2 macrophages, and levels of MMP9 and MMP12 in bronchoalveolar lavage were increased in PTB patients with smoking. Between-group analysis showed that the frequency of M1 macrophages was higher in non-smoker PTB patients while more M2 macrophages were found in smokers without PTB, as compared to the non-smoker healthy controls. Bacille Calmette-Guérin (BCG) infection in CS extract (CSE)-incubated MH-S cells further enhanced secretion of M1-related (iNOS, IFN-γ and TNF-α) and M2-related (TGF-β and IL-10) cytokines, reactive oxygen species (ROS) production and cellular apoptosis, concomitantly with up-regulation of MMP9 and MMP12, but not TIMP1. Moreover, BCG infection in acutely CS-exposed mice promoted macrophage polarization towards both M1 and M2 phenotypes, along with increased lung inflammatory infiltration. MMP9 and MMP12, but not TIMP1, were further up-regulated in lung tissues and BAL fluid after BCG infection in this model. Taken together, Mtb Infection promoted CS-exposed macrophages to polarize toward both M1 and M2 phenotypes, along with enhanced production of MMP9 and MMP12. These findings provide insights into the mechanistic interplay between CS exposure and tuberculosis in the pathogenesis of COPD.